Risk Factors for Anaplastic Thyroid Carcinoma: A Case Series From a Tertiary Referral Center for Thyroid Surgery and Literature Analysis - Graceffa, Giuseppa; Salamone, Giuseppe; Contino, Silvia; Saputo, Federica; Corigliano, Alessandro; Melfa, Giuseppina; Proclamà, Maria Pia; Richiusa, Pierina; Mazzola, Sergio; Tutino, Roberta; Orlando, Giuseppina; Scerrino, Gregorio (Frontiers in Oncology, 2022)
Anaplastic carcinoma of the thyroid (ATC) is a very rare and extremely aggressive disease with a very poor prognosis. Several risk factors have been hypothesized, but there is no clear-cut literature data on it. We reviewed the literature concerning risk factors for ATC and analysed the institutional database from 2005 to 2022. In total, 15 papers were suitable for review, while the retrospective data collection search, conducted on our institutional database, provided 13 results. In our experience, in agreement with literature data, ATC seems to be a neoplasm peculiar to old age (in our database mean age is 72 years), with a higher prevalence in subjects with a low level of education and a long history of multinodular goiter (MNG). The role of cigarette smoking and blood group, hypothesized on some literature data, was more uncertain, although the small sample size evaluated probably had a great influence on these results. The higher incidence of the disease in individuals with a history of MNG could suggest more aggressive choices in the treatment of a benign disease, in contrast to current practice. However, this may be a highly questionable point considering that ATC accounts for no more than 2% of all thyroid neoplasms in surgical departments, even those dedicated to endocrine neck surgery. Further studies are therefore necessary for a step forward in this direction.